Benefit of electron beam therapy in combination with medium‐dose systemic corticosteroid as a palliative treatment for elderly patients with blastic plasmacytoid dendritic cell neoplasm: case report and review of the literature. (1st March 2019) - Kinoshita‐Ise, M.; Uchida, R.; Shioiri, M.; Ohmori, Y.; Takayama, N.; Ohyama, M.
Abstract: Click here for the corresponding questions to this CME article.